Phage-Derived Endolysins Against Resistant Staphylococcus spp.: A Review of Features, Antibacterial Activities, and Recent Applications - Mina Golban; Javad Charostad; Hossein Kazemian; Hamid Heidari (Infectious Diseases and Therapy)
Abstract Antimicrobial resistance is a significant global public health issue, and the dissemination of antibiotic resistance in Gram-positive bacterial pathogens has significantly increased morbidity, mortality rates, and healthcare costs. Among them, Staphylococcus, especially methicillin-resistant Staphylococcus aureus (MRSA), causes a wide range of diseases due to its diverse pathogenic factors and infection strategies. These bacteria also present significant issues in veterinary medicine and food safety. Effectively managing staphylococci-related problems necessitates a concerted effort to implement preventive measures, rapidly detect the pathogen, and develop new and safe antimicrobial therapies. In recent years, there has been growing interest in using endolysins to combat bacterial infections. These enzymes, which are also referred to as lysins, are a unique class of hydrolytic enzymes synthesized by double-stranded DNA bacteriophages. They possess glycosidase, lytic transglycosylase, amidase, and endopeptidase activities, effectively destroying the peptidoglycan layer and resulting in bacterial lysis. This unique property makes endolysins powerful antimicrobial agents, particularly against Gram-positive organisms with more accessible peptidoglycan layers. Therefore, considering the potential benefits of endolysins compared to conventional antibiotics, we have endeavored to gather and review the characteristics and uses of endolysins derived from staphylococcal bacteriophages, as well as their antibacterial effectiveness against Staphylococcus spp. based on conducted experiments and trials.